An integrated parasitology: revealing the elephant through tradition and invention. Issue 4 (April 2015) - Hoberg, Eric P.; Agosta, Salvatore J.; Boeger, Walter A.; Brooks, Daniel R.
Highlights An integrated parasitology drives fundamental insights about the changing biosphere. A correct taxonomy is the gateway to history, ecology, and biogeography. Systematics and archives are essential to explaining global biodiversity.